The Role of the Millennial Generation as Candidates for Legislative Members in 2024 Election - Nur, Hasruddin; Jalal; Amir, Arfenti; Suardi; Kasim, Hasanudin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The millennial generation has great potential to serve as legislative candidates in the 2024 election. They bring new perspectives, innovative thinking, and technological skills that can make a positive contribution to the legislative process. This research aimed to analyze and describe the role of the millennial generation as legislative candidates in the 2024 election. This research used descriptive qualitative techniques, which required a literature review that involved searching for relevant reading material in books or articles. This research shows that there was a challenge for the millennial generation in facing the 2024 election, namely that there is a negative stigma, sometimes they are said to tend to be lazy, anti-social, and even seen as not understanding politics and not caring about national conditions, although this is not entirely true. Motives and encouragement of the Millennial Generation to Become Candidates for Legislative Membership in 2024 are due to the hope that this generation can bring more adaptive, inclusive, and progressive changes to the policy-making process, such as the call to be involved in the political process, feel better represented, and hope for change. The potential for the millennial generation becomes legislative members in the 2024 election, because they have creativity and innovation, progressive thinking, and acceptance of the millennial generation in society in the 2024 election.